A modified active disturbance rejection control strategy based on cascade structure with enhanced robustness. (October 2022) - Liu, Yifan; Liu, Gang; Zheng, Shiqiang; Li, Haitao
Abstract: Active disturbance rejection control (ADRC) is considered to be a common control method in the presence of external disturbances and uncertainties. This work proposes a modified ADRC control strategy to further enhance robustness to uncertainties. First, the cascade structure of modified ADRC composed by two control loops is introduced. Two extended state observers that can be tuned independently are arranged in a cascade structure. The outer loop observer provides system state estimation to build the feedback controller, and the inner loop observer deals with the generalized disturbance. Then, the enhanced robustness is verified by the improved sensitivity in the intermediate frequency range. Finally, for the axial magnetic bearing system with unstable system dynamics, the variation trend in maximum sensitivity with different control parameters is explained in the simulation. The experiments are conducted under varying disturbances and parameter uncertainty to verify the enhanced control performance. Highlights: A modified active disturbance control method is proposed to enhance the system robustness. The enhanced robustness to uncertainty is demonstrated by sensitivity analysis. The noise reduction performance is evaluated by the system high frequency gain. The control performance is verified on magnetic bearing system under different loads and disturbances.